Criminal History and Adverse Childhood Experiences in Relation to Recidivism and Social Functioning in Multi-problem Young Adults - Van Duin, Laura (Criminal justice and behavior, 2021)
This study examines the relationship between criminal history and adverse childhood experiences (ACEs) and how they collectively predict (a) recidivism and (b) positive social functioning among multi-problem young adults. Criminal records and self-report data regarding ACEs and adult education/employment and quality of life (QoL) were collected for 692 multiproblem young adults (18–27 years). Results indicated that an extensive criminal history was related to non-violent and violent recidivism and lack of involvement in education/employment in young adulthood. On the contrary, a higher number of ACEs was related to lower QoL later in life, while this was not associated with recidivism or education/employment. These findings highlight again that past criminal behavior is a strong predictor of future criminality, particularly within this group of young adults with multiple problems. Furthermore, experiencing negative events in childhood shows to have long-term negative effects on QoL even for these individuals who already experience multiple life problems. Implications are discussed.